Telemetry Tracking of Two Resplendent Quetzals (Pharomachrus mocinno mocinno) at a mountain area of Baja Verapaz, Guatemala - Bustamante, Michelle (Universidad de San Carlos de Guatemala, 2024)
Telemetry tracking provides essential insights into avian movements and habitat preferences, aiding the identification of critical resources and conservation areas for endangered species such as the Resplendent Quetzal. In this study, we tracked two radio-tagged Resplendent Quetzals in a mountainous cloud forest region containing national protected areas, private reserves, and indigenous lands. Both individuals primarily remained within the protected Biotopo del Quetzal reserve and nearby areas for approximately five months; however, during the non-breeding season, one individual exhibited increased mobility, moving outside the reserve for three months and utilizing lower-elevation areas up to 5.5 km away. These areas are embedded in a modified landscape, comprising agricultural fields, roads, and human settlements. Together with previous telemetry data from Central America’s quetzal populations, these findings support the occurrence of seasonal migratory behavior in this species, indicating reliance on distinct habitats at different times of the year. Establishing biological corridors could provide safe passage between these habitats, facilitating access to vital foraging and roosting sites while mitigating genetic isolation effects through enhanced connectivity and genetic resilience. Key non-protected sites within the study area, such as Ranchitos del Quetzal and forest patches along the Panimá River basin, offer valuable opportunities for targeted conservation aimed at improving habitat connectivity, safeguarding critical resources, and engaging local communities. Finally, preserving and restoring plant species identified as primary food sources should be prioritized in protected and adjacent areas to ensure adequate nutrition for Quetzals throughout their migratory and breeding cycles.